Panama : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Panama. (IMF Staff Country Reports; Country Report, 2019)
Panama has had the longest and fastest economic expansion in recent Latin American history. The economy has expanded at an average rate of about 6 percent per annum over the last quarter of a century, with Panama achieving one of the highest per capita income in Latin America. More recently, GDP grew by about 5 1\2 percent in 2017 (driven by the expanded Canal), and then slowed to 3 3/4 percent (y/y) in H1-2018. Inflation remained subdued, reaching almost 1 percent (y/y) in September 2018. The external current account deficit stayed at 8 percent of GDP in 2017, mostly covered by FDI. The fiscal position continued to be strong, with the overall deficit of the non-financial public sector (NFPS) at about 1 1\2 percent of GDP. Credit growth has decelerated as financial conditions have started to tighten.